Conceptualizing ICT leadership practices: A study in Colombian higher education - Gary Alberto Cifuentes (Arizona State University, 2016)
Based on an empirical study on ICT leadership for educational innovation, this document analyze some leadership practices that become relevant in the context of higher education institutions. This paper explores specific units within institutions that promote innovation with ICT. These units are appointed to lead educational innovation with ICT beyond technical support, focusing instead in transforming teaching practices with technology. As it is shown in this work, the analysis of these leadership practices reveals a strong relationship with higher education policies. The findings of this study mention four characteristics of these units: their knowledge is both centralized and distributed; they participate in the translation of education policies; they experience external demands; finally, they have a political nature beyond their administrative functions. This work shows that these units-underexplored in the current literature-become relevant for studying political and organizational conditions involved in educational innovation supported by technology.